Kikuchi pattern analysis of noncentrosymmetric crystals. (1st October 2015) - Nolze, G.; Grosse, C.; Winkelmann, A.
<x xml:space="preserve">Abstract</x> Different models of Kikuchi pattern formation are compared with respect to their applicability to noncentrosymmetric crystals, and the breakdown of Friedel's rule in experimental electron backscatter diffraction (EBSD) patterns is discussed. Different AIIIBV semiconductor materials are used to evaluate the resulting asymmetry of Kikuchi band profiles for polar lattice planes. By comparison with the characteristic etch pit morphology on a single‐crystal surface, the polar character of the measured lattice planes can be assigned absolutely. The presented approach enables point‐group‐resolved orientation mapping, which goes beyond the commonly applied Laue group analysis in EBSD.